Redescription of Arcotheres pernicola (Bürger, 1895) (Crustacea: Decapoda: Brachyura: Pinnotheridae) from the oyster Magallana gryphoides (Schlotheim, 1820) in India - Trivedi, Jigneshkumar N.; Gosavi, Swapnil; Vachhrajani, Kauresh D.; Ng, Peter K. L. (Zootaxa, 2019)
The identity of Arcotheres pernicola (Bürger, 1895) (Pinnotheridae), a pea crab supposedly associated with the mussel Perna, has been unclear as the type specimen is in poor condition. Specimens collected from the oyster Magallana gryphoides (Schlotheim, 1820) from Alibaugh, Maharashtra state, India, are here referred to A. pernicola and the species is redescribed and refigured. Its affinities with allied congeners are also discussed.